PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT: UPAYA PENCEGAHAN DAN PEMBERANTASAN SARANG NYAMUK DI PERUMAHAN BPD GRAHA BINTANG TIMUR DISTRIK SENTANI KABUPATEN JAYAPURA - Maklon Warpur; Natan Baransano (LPPM Uncen, 2023)
The counseling activities Improving Clean and Healthy Behavior through Environmental Cleanliness as an Effort to Prevent and Eradicate Mosquitoes in Residents of BPD Graha Bintang Timur, Sentani District Jayapura Regency, have been conducted on May 7, 2022. The activity aims to motivation the community about the importance of maintaining cleanliness and environmental health in preventing and eradicating malaria mosquito nests, as well as to provide understanding to the public in protect the environment so as to avoid malaria caused by an unhealthy environment. While the benefit of this activity is to increase public understanding in maintaining environmental health, as well as fostering public awareness in clean and healthy living behavior. The methods used in this activity were lectures, discussions and questions as well as answers. The implementation of counseling activity of environmental health began with self-introduction by the team of presenters, then the team of presenters tried to dig basic knowledge of the community about sanitation and environmental hygiene. With the existence of this community service activity on environmental health, hopefully it can increase the knowledge of the residents of BPD Graha Bintang Timur Sentani about a style of healthy life for the sake of creating a better quality of life, and is able to increase the awareness of the people of BPD Graha Bintang Timur Sentani to participate actively in maintaining cleanliness and environmental health.Keywords: sanitation; environmental cleanliness; BPD Graha Bintang Timur Sentani